SOCIAL PROTECTIONS IN HEALTH AND EDUCATION THROUGH THE HOPE FAMILY PROGRAM: A CASE STUDY IN WANAYASA VILLAGE, WANAYASA SUB-DISTRICT, PURWAKARTA REGENCY - Yuningsih, Yuyun; Sumardani, Sumardani; Hani, Ummi (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2018)
Hope Family Program (HFP) commenced in 2007 served as a part of social security for the very poor households (VPH) to get their descent out from the poverty trap. HFP is focused on health and education sectors since both sectors are the core for life improvement of society. It has been implemented in 33 provinces with varying effectiveness. The purposes of this study were to identify the effectiveness of HFP implementation in Wanayasa Village, Wanayasa Sub-district, Purwakarta Regency and to reveal various related aspects that could potentially impact the success of the program. The study was conducted using quantitative descriptive approach by involving 41 participants from VPH joining to HFP implemented in the village as the respondents. A SWOT analysis was performed to explore the underlying issues as to the effectiveness, coverage, and sustainability of the program. In most cases, the respondents acknowledged that HFP had been well implemented and the received cash was sufficient to cover the expenses for children education and health care. The performed SWOT analysis leads to some offered approaches for the program improvement in the village